The integrating chatbots in library services for balancing efficiency and interpersonal communication - Mustofa, Muhamad Bisri; Efendi, Nasrul; Sentiana, Fegi; Wuryan, Siti; Makmun, Fariza (Jurnal Kajian Informasi dan Perpustakaan, 2025)
Background: The increasing use of technology in libraries has made chatbots a solution for responding to questions and providing information more quickly and efficiently. However, the use of chatbots has the potential to reduce the personal aspect that has been inherent in conventional interactions between librarians and library users. Purpose: This study examines the application of chatbots in library services and their impact on interpersonal communication. Methods: This study employed a systematic literature review method, searching Google Scholar and Taylor and Francis Online databases. Of the 125 articles identified initially, 15 articles met the inclusion criteria through a PRISMA-based selection process and were used as the primary data sources. The researcher chose this approach because it ensured a systematic and transparent process for identifying, evaluating, and synthesizing the literature. Results: The study results showed that chatbots generally provided a positive user experience, particularly in terms of ease of use, flexibility of access, speed, accuracy of information, and responsiveness to student needs. Conclusion: In addition to improving service quality, chatbots also contributed to operational efficiency on campus. However, there are several limitations, including the chatbot’s inability to understand complex or ambiguous questions, limitations in capturing conversational context and interaction history, and a high dependence on data completeness and accuracy, which can potentially result in inaccurate information. Implication: This study implies that libraries should implement chatbots as supportive tools alongside librarians to enhance service efficiency while preserving interpersonal communication for complex user needs.